Study of pain scores and need for rescue analgesia with intrathecal fentanyl as an adjuvant with 0.5% hyperbaric bupivacaine for cesarean section - Thrupthi BP; Memon, Nazima Y; Niteen K Nandanwankar; Yennawar SD; Ajay L Jogdand; Juhi P Bagga (Asian Journal of Medical Sciences, 2022)
Background: Cesarean section contributes to the major part of surgeries taking place in any hospital now a days. Hence, improving anesthesia in cesarean section is of paramount importance. Intrathecal fentanyl can produce rapid, profound analgesia for cesarean section, early labor with minimal side effects. It also has minimal respiratory depressant effect on fetus. Present study was aimed to study pain scores and need for rescue analgesia with intrathecal fentanyl as an adjuvant with 0.5% hyperbaric bupivacaine for cesarean section. Aims and Objectives: Primary Objective was to evaluate intrathecal fentanyl as an adjuvant with 0.5 % hyperbaric Bupivacaine for caesarean section. The secondary objective was to compare onset and duration of sensory and motor blockade as well as to assess pain scores, analgesic requirements and side effects. Materials and Methods: The present study was hospital-based randomized double-blind control study conducted in pregnant women of 18–35 years age, 50–70 kg weight, ASA-II, posted for elective cesarean section. 60 patients were randomly divided into Group I (study group, n=30, receiving 0.5 % hyperbaric bupivacaine 1.6 ml+intrathecal fentanyl 0.4 ml/20 mcg) and Group II (control group, n=30, receiving 0.5% hyperbaric bupivacaine 1.6 ml+0.4 ml normal saline). Results: The difference in mean time for onset of sensory block, onset of motor block, maximum time taken to achieve highest level of sensory analgesia, total duration of motor block, and degree of motor block was statistically insignificant. The difference in mean duration of time to sensory regression was statistically highly significant (P<0.0001). VAS score was used to assess pain postoperatively initially every 5 min then every 30 min up to 5 h. VAS score in post-operative period was less in Group I and difference was statistically significant. Mean Apgar Score at 1 and 5 min were comparable in both the groups with no statistically significant difference. Diclofenac consumption was significantly decreased in Group I as compared to group II. Conclusion: We conclude that the 0.5% hyperbaric Bupivacaine 8 mg with Fentanyl 20 μg is safe, effective, superior for spinal anesthesia, provided more longer duration of analgesia and significantly reduced number of rescue analgesia doses in cesarean section.